Prevalence and Associated Factors of HPV DNA Test Status of Women Attending a Tertiary Cancer Hospital of Central Nepal - Acharya, Bijaya Chandra; Subedi, Hemnath; Gurung, Sarita Rana; Pandey, Greta; Rana, Asmita; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2025)
Background Human papillomavirus (HPV) is a significant cause of cervical cancer, and understanding the factors associated with HPV infection in women is crucial for preventive strategies. This study aimed to find the prevalence and associated factors of HPV DNA test results among women aged 30-50 years. Methods An analytical cross-sectional study was conducted at the BP Koirala Memorial Cancer Hospital from July 2024 to March 2025. Ethical approval was obtained from the Nepal Health Research Council (Ref No. 53-2024). Informed consent was collected from all participants. A total of 1,000 women aged 30-50 years were tested for HPV DNA. The dependent variable was HPV DNA status. Data were analyzed using SPSS software, and statistical associations were determined using Chi-square test. A p-value of <0.05 was considered as statistically significant. Results The prevalence of HPV DNA positivity was found to be 10% (95% CI: 8.14% - 11.8% ). Significant associations were observed between HPV positivity and early sexual debut (p-value= 0.048), contraceptive use (p-value < 0.001), and BMI (p -value= 0.018), sexual bleeding during intercourse was also strongly associated with HPV DNA status (p -value < 0.001). Conclusions The study highlights early sexual activity, contraceptive use, and BMI as significant factors associated with HPV DNA positivity in women aged 30-50 years. These findings suggest the need for targeted public health interventions focused on sexual health education, contraceptive counseling, and HPV screening for women in this age group.